Pengaruh Customer Satisfaction dan Trust Terhadap e-WOM: Commitment Sebagai Variabel Intervening (Studi Pada Mahasiswa Universitas Negeri Padang) - Tri Putri Parnataria; Abror Abror (Jurnal Kajian Manajemen dan Wirausaha, 2019)
This study analyzes:  (1) the effect of customer satisfaction on trust (2) the effect of customer satisfaction on commitment (3) the effect of trust on commitment (3) the effect of trust on e-wom (4) the effect of customer satisfaction on ewom (5) the effect of trust on ewom (6) the effect of  commitment on e-wom.This type of research is causative research. The population in this study was all students from Padang State University who used the online shop Lazada. By using purposive sampling we use 150 customers as the respondent. This study used online questionnaires as the data collection instrument, This study analyzed the data by using structural equation modeling (SEM) with smart PLS 3.0 as the software package. The results of his study indicate that: (1) customer satisfaction has a significant effect on trust (2) customer satisfaction has a significant effect on commitment (3) trust has a significant effect on commitment (4) customer satisfaction has a significant effect on e-wom (5) trust has a significant effect on e-wom (6) commitment has a significant effect on e-wom. Keywords:Customer satisfaction, trust, commitment, electronic word of mouth.